2008
DOI: 10.1016/j.palaeo.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Clay-mineral record in Lake Baikal sediments: The Holocene and Late Glacial transition

Abstract: Abstract:We analyse the clay-mineralogical composition of two 1-m long cores from elevated plateaus in the southern and northern basins of Lake Baikal. Our aim is to test the limits of classically used clay proxies for climate reconstructions. Mineralogical signature is determined by X-ray diffraction on oriented aggregates from Holocene and Late Glacial sediments. Mineralogical results are presented on a palaeomagnetic-derived time scale. Sampling at a centimeter resolution allows for a sub-millenial order re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The background noise of the X-ray patterns was removed and the line position, intensity peak, and integrated area were calculated with DIFFRACplus EVA software (Bruker). Semiquantitative estimations of the main clay species were obtained on EG runs according to the methods of Biscaye (1965), Thorez (1976), , and Fagel & Boës (2003).…”
Section: E T H O D Smentioning
confidence: 99%
“…The background noise of the X-ray patterns was removed and the line position, intensity peak, and integrated area were calculated with DIFFRACplus EVA software (Bruker). Semiquantitative estimations of the main clay species were obtained on EG runs according to the methods of Biscaye (1965), Thorez (1976), , and Fagel & Boës (2003).…”
Section: E T H O D Smentioning
confidence: 99%
“…In the former the quartz and feldspar mostly display a schistose structure with melted rims, with rare or no grains of crystal form, while in the latter feldspar grains with cleavage can be found. Besides, except illite there are no other clay minerals such as kaolinite and montmorillonite found that are common in sandstone and mudstone (Chamley, 1989;Awwiller, 1993;Guyot et al, 2007;Fagel, 2007). The illite occurs in a filamented or untypical lepidosome form (Plate 1-4-5).…”
Section: Mineralogic and Petrologic Characters Of Burnt Rocksmentioning
confidence: 99%
“…On the other hand, much research has been done on lacustrine mineral sediments, but mostly glacial lake sediments [3], [4]. Sediment grain size distribution [5], mineral composition and clay minerals alone [6], [7] or combined with other parameters are widely used to reconstruct past climates from marine and lacustrine sedimentary record [1]- [4], [8]- [10]. Better than bulk mineral composition, clay minerals may serve as effective tools to establish the origin of fine-grained terrigenous sediment of seas [11,12] and lakes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Better than bulk mineral composition, clay minerals may serve as effective tools to establish the origin of fine-grained terrigenous sediment of seas [11,12] and lakes [13]. Review of scientific literature revealed that clay minerals, their ratios and variety of mineralogical indices, as crystallinity degree of illite (Kübler index), crystallinity degree of chlorite (Àrkai index), P index (describes mutual relations between neoformed and detrital mineral phases) as well as others may be applied for sedimentological and paleoclimatic reconstructions [6,7], [15,16].…”
Section: Introductionmentioning
confidence: 99%